Conflict and Sovereignty. The Debate between the United States and the European Union - Kuniński, Miłowit (Civitas. Studia z filozofii polityki, 2009)
Certainly we are dealing with a profound and long-lasting crisis at the core of the Western World, caused by the fall of the communist system – as many have already pointed out – which changed the previous distribution of power and enabled a clearer and more open redefinition of the interests of its main political actors. This crisis will be characterized by irregular outbursts of aggressive activity, often far exceeding the norms of diplomatic correctness, by periods of collaborative effort, particularly if the West faces serious threats on a more global scale and has to deal with serious political games. It is certain that the main source of this present crisis is the rivalry that has been waged on various fronts between the US and the European Union. It can be therefore affirmed that, from the point of view of the logic of political transformation, the Union must aim toward an external sovereignty. This process will certainly be a long one, and will undoubtedly involve recurring frictions between the European Union and the United States. This will be the symptom of the process of building the sovereignty in opposition to a state whose legal and international sovereignty cannot be questioned, and whose practical sovereignty has been expressed in the active participation in the international arena for almost 200 years.